2021
DOI: 10.1186/s12859-021-04170-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimating colocalization probability from limited summary statistics

Abstract: Background Colocalization is a statistical method used in genetics to determine whether the same variant is causal for multiple phenotypes, for example, complex traits and gene expression. It provides stronger mechanistic evidence than shared significance, which can be produced through separate causal variants in linkage disequilibrium. Current colocalization methods require full summary statistics for both traits, limiting their use with the majority of reported GWAS associations (e.g. GWAS Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Several investigators have shied away from recommending the use of eQTL information to prioritize target tissues in GWAS, 42 , 50 citing the tissue-sharing of cis -eQTLs in a large fraction of trait associations as one reason. 51 Recent work by us 52 and others 4 , 53 , 54 has demonstrated the existence of tissue-specific eQTLs and shown potential for leveraging those eQTLs to understand broad patterns of tissue enrichment for human complex traits. For example, Majumdar et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have shied away from recommending the use of eQTL information to prioritize target tissues in GWAS, 42 , 50 citing the tissue-sharing of cis -eQTLs in a large fraction of trait associations as one reason. 51 Recent work by us 52 and others 4 , 53 , 54 has demonstrated the existence of tissue-specific eQTLs and shown potential for leveraging those eQTLs to understand broad patterns of tissue enrichment for human complex traits. For example, Majumdar et al.…”
Section: Discussionmentioning
confidence: 99%
“… 54 Similarly, other groups have shown enrichments of complex traits for biologically relevant tissues by using colocalization or mediation approaches on eQTL data. 4 , 53 , 55 However, as a result of the inability of existing methods to fully evaluate allelic heterogeneity and LD, the extent of tissue specificity of eQTLs has not been previously fully explored or harnessed. Specifically, it remains an open question whether the observed tissue-specific enrichments are driven by a small number of genes known to possess eQTLs only in specific tissues or by pervasive patterns of tissue specificity confounded by allelic heterogeneity and LD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the GWAS Catalog only reports the lead variant for each locus, and this variant is not necessarily identical to the causal variant for the association, we performed an LD expansion from each top SNP to identify additional possible causal variants. Broad ancestry as reported in the GWAS Catalog was mapped to a 1000 Genomes superpopulation following methods we described recently [23]. For each associated SNP in the GWAS Catalog, an LD expansion was performed to identify SNPs within 1 Mb with LD r 2 ≥ 0.5 in the corresponding 1000 Genomes super-population.…”
Section: Methodsmentioning
confidence: 99%
“…GWAS Catalog Experimental Factor Ontology (EFO) terms and disease terms curated from the literature were mapped to the 2020 MeSH thesaurus vocabulary using the approach outlined previously [26]. To allow for inexact matches in MeSH terms (e.g., hypertension and systolic blood pressure), we use two similarity metrics: Lin-Resnik average similarity with a cutoff value of 0.75 [26,27] and odds ratio of MeSH term co-occurrence in the same PubMed article with a cutoff of 20 [23]. We count a match between an article identified in our systematic review and a GWAS study if any GWAS Catalog association satisfies the following criteria: (1) The reported variant in the GWAS Catalog has LD R 2 ≥ 0.5 to at least one curated variant, and (2) the reported trait in the GWAS Catalog has similarity to a main or manually curated disease from the PubMed abstract, meeting or exceeding the cutoff value.…”
Section: Methodsmentioning
confidence: 99%